Analisis Kuantitatif Prestasi Belajar Siswa SMA Swasta di Tinjau Dari Kecerdasan Spiritual dan Motivasi Belajar di Sekolah Minggu Buddha (SMB) Chong-De Se Sumatera Utara - Joli Joli; Ida Ayu Gede Yadnyawati; Muljadi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2022)
The purpose of this study was to determine the effect of spiritual intelligence and learning motivation on student achievement of Buddhist Sunday School (SMB) Chong-De North Sumatra. This study uses multiple regression analysis to determine the effect of spiritual intelligence (X1) and learning motivation (X2) on student achievement (Y). In this study the determination of the sample using quota sampling technique with the number of samples used in this study as many as 198 respondents. This study uses primary data, data is collected by distributing questionnaires to respondents via google forms. Testing the research hypothesis using SPSS 20.0 for Windows.The results showed that spiritual intelligence (X1) had a positive effect on student achievement (Y) Buddhist Sunday School (SMB) Chong De North Sumatra with a correlation coefficient score of ry1 = 0.732 and a determination coefficient score of r2y1 = 0.535. Learning motivation (X2) has a positive effect on student achievement (Y) Buddhist Sunday School (SMB) Chong De North Sumatra with a correlation coefficient score of ry2 = 0.852 and a determination coefficient score of r2y2 = 0.727. Spiritual intelligence (X1) and learning motivation (X2) have a positive and significant effect on student achievement (Y) Buddhist Sunday School (SMB) ChongDe North Sumatra with a correlation coefficient score of ry1,2 = 0.879 and a determination coefficient score of r2y1,2= 0.772. The regression equation in this study is as follows: 1.2 = 23.008 + 0.258 X1 + 0.626 X2.Based on these results, to optimize student achievement, policies and regulations are needed to increase spiritual intelligence and learning motivation.